2020
DOI: 10.1002/lsm.23253
|View full text |Cite
|
Sign up to set email alerts
|

Oxymetazoline and Energy‐Based Therapy in Patients with Rosacea: Evaluation of the Safety and Tolerability in an Open‐Label, Interventional Study

Abstract: Background and Objectives The objectives of this study were to evaluate the safety, tolerability, and efficacy of oxymetazoline hydrochloride cream, 1% (oxymetazoline) when used as an adjunctive treatment with energy‐based therapy for patients with moderate to severe facial erythema associated with rosacea. Study Design/Materials and Methods In this Phase 4, multicenter, interventional, open‐label study, eligible patients received one of four energy‐based therapies (potassium titanyl phosphate laser, intense p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…The combination of laser-and light-based therapies and other therapies has also been investigated in recent studies. The findings of a phase 4, multicenter, interventional, open-label study with 46 patients suggest the benefit of oxymetazoline as adjunctive therapy with energy-based therapy for the treatment of moderate to severe persistent facial erythema associated with rosacea [54]. A retrospective study including 31 subjects revealed that the combination of pulsed dye laser and 1.0% oxymetazoline cream reduced erythema and telangiectasias both safely and effectively [55].…”
Section: Laser-and Light-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of laser-and light-based therapies and other therapies has also been investigated in recent studies. The findings of a phase 4, multicenter, interventional, open-label study with 46 patients suggest the benefit of oxymetazoline as adjunctive therapy with energy-based therapy for the treatment of moderate to severe persistent facial erythema associated with rosacea [54]. A retrospective study including 31 subjects revealed that the combination of pulsed dye laser and 1.0% oxymetazoline cream reduced erythema and telangiectasias both safely and effectively [55].…”
Section: Laser-and Light-based Therapiesmentioning
confidence: 99%
“…Combination therapy to target specific features is necessary to achieve effective treatment, especially in patients with severe rosacea or multiple rosacea features [13,14]. Oral therapy combined with topical therapy [83], laser-/lightbased therapy combined with topical therapy [54], and a combination of topical therapies [84] have all been documented in recent publications. Fractional microneedling radiofrequency, a new device in dermatology, has also been used to treat recalcitrant papulopustular rosacea combined with pulsed dye laser and oral isotretinoin [85].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…3 Use of oxymetazoline as adjunctive therapy with potassium-titanyl-phosphate (KTP) lasers, 595nm pulse dye laser (PDL), and IPL has been demonstrated to be well tolerated and efficacious in further helping to reduce facial erythema. 12 , 13 …”
Section: Topical Medical Therapiesmentioning
confidence: 99%
“…[10] [11] In addition, the application of oxymetazoline in cream form as adjunctive therapy has been evaluated as safe and well tolerated, and reduces facial erythema in patients with moderate to severe facial erythema associated with rosacea. [12] Based on current research, topical alpha-adrenergic receptor agonist therapies have been shown to be safe and effective and are currently the only agents offered specifically for facial erythema associated with rosacea. Topical 1% oxymetazoline should now be included in the arsenal of medications for facial erythema in rosacea, as data suggest that it is an effective alternative with minimal side effects compared to previously approved topical medications.…”
Section: New Applications -A Reviewmentioning
confidence: 99%